2018
DOI: 10.17116/jnevro2018118091106
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and epigenetics of attention deficit hyperactivity disorder

Abstract: Синдром дефицита внимания и гиперактивности (СДВГ)-сложное поведенческое расстройство [1] с высокой степенью наследуемости [2]. Оно характеризуется невнимательностью, гиперактивностью и импульсивностью [1]. Согласно DSM-5 cимптомы СДВГ возникают в возрасте до 12 лет, вызывая значительные нарушения социальных, академических и профессиональных функций на протяжении всей жизни [3]. Распространенность СДВГ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The five major neuropsychiatric disorders are bipolar disorder (BP), MDD, ADHD, Schizophrenia (SCZ), and PTSD; many of these disorders have overlapping symptomatology or high comorbidity rates making it challenging to make a definite diagnosis. Each one of the neuropsychiatric disorders has been extensively linked to genetics in that having a parent or sibling with the neuropsychiatric disorders increases the risk of development of that disorder (Picchioni et al ; Mustafin et al ; Stapp et al ; Isaksson et al ; Elsayed et al ). Similar to the role of NE and DβH in substance abuse, DβH involvement in neuropsychiatric disorders is linked to alterations in plasma/sera DβH activity (Table ), while direct pharmaceutical interventions in NE signaling (antagonist/agonist) or DβH (inhibitor) are frequency employed in treatment (Maletic et al ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…The five major neuropsychiatric disorders are bipolar disorder (BP), MDD, ADHD, Schizophrenia (SCZ), and PTSD; many of these disorders have overlapping symptomatology or high comorbidity rates making it challenging to make a definite diagnosis. Each one of the neuropsychiatric disorders has been extensively linked to genetics in that having a parent or sibling with the neuropsychiatric disorders increases the risk of development of that disorder (Picchioni et al ; Mustafin et al ; Stapp et al ; Isaksson et al ; Elsayed et al ). Similar to the role of NE and DβH in substance abuse, DβH involvement in neuropsychiatric disorders is linked to alterations in plasma/sera DβH activity (Table ), while direct pharmaceutical interventions in NE signaling (antagonist/agonist) or DβH (inhibitor) are frequency employed in treatment (Maletic et al ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…Thus, as described in Table 2, some genes related to psychiatric disorders can also be thought of as a possible link between violent behaviour and sleep disruption (Agorastos et al, 2019;Bhatti et al, 2015;Cupertino et al, 2017;Killgore, 2013;Kohannim et al, 2012;Lamont et al, 2007;Motomura et al, 2013;Mustafin et al, 2018;Rautiainen et al, 2016;Reijnders et al, 2017;Taki et al, 2012;Tiihonen et al, 2015;Zhang et al, 2019).…”
Section: Genes Violent Behaviours and Sleepmentioning
confidence: 99%
“…It is known that the synaptosomal-associated protein 25 (SNAP25), together with syntaxin-1A (STX1A) and vesicle-associated membrane protein 2 (VAMP2), mediates neurotransmitters released by the fusion of synaptic vesicles [162,163]. It was also already reported that alterations in gene expression of SNAP25 in mammals are associated with schizophrenia-like behavior [164], and sequence variations in the SNAP25 locus are associated with attention-deficit/hyperactivity disorder (ADHD) [165][166][167].…”
Section: Synaptic Vesicle Trafficking and Exocytosismentioning
confidence: 99%